Adventure Tourism Study: Implications for Nepal (Journal of Tourism and Himalayan Adventures, 2019)
This study has assessed the definitions, historical development and scope of adventure tourism globally and its implications for Nepal. It is based on the secondary literature review and analysis that refers to some of the imminent text books and reports. Further, it has focused on the economic prospects associated with the adventure tourism activities and its benefits to the destination and nation. The study has suggested some of the essential prerequisites that are needed to be maintained for the establishment of Nepal as a destination of adventure tourism at a high ranking spot in the developing world.